Severity of emergency department presentations due to acute drug toxicity in Europe: a longitudinal analysis over a 6-year period (2014–2019) stratified by sex. (10th November 2022) - Miró, Òscar; Burillo-Putze, Guillermo; Schmid, Yasmin; Salgado, Emilio; Liechti, Matthias E.; Dines, Alison M.; Giraudon, Isabelle; Heyerdahl, Fridtjof; Hovda, Knut Erik; Vallersne, Odd Martin; Eyer, Florian; Wood, David M.; et al.
Abstract : Objective: To investigate whether the severity of acute recreation drug toxicity presentations to emergency departments (EDs) in Europe has changed in recent years and to uncover potential sex differences. Design: We analysed presentations to 36 EDs in 24 European countries relating to acute recreational drug toxicity, with separate analysis for presentations involving lone use of cannabis, cocaine, and heroin. As severity markers, we calculated rates of hospitalization, admission to ICU, intubation, and death by annual quarters between 2014 and 2019. Trends on severity over time were estimated by logistic regression. Differences between men and women were assessed by interaction. Sensitivity analysis was performed including only EDs that provided data for all 24 quarters. Analyses of intoxications taken altogether were adjusted by age and sex, while of lone intoxications being also adjusted by ethanol co-ingestion. Results: There were 43 633 presentations (median age = 31 years, interquartile range = 25–40 years, men = 76.5%) resulting in 10 344 hospitalizations (23.9%), 2568 ICU admissions (5.9%), 1391 intubations (3.2%), and 171 deaths (0.39%). Hospitalization, ICU admission and death did not differ by sex, but intubation was more frequent in men (3.4% vs. 2.3%, P < 0.001). No significant changes in the severity of drug intoxications over time were found when considered altogether, neither for lone cannabis (n = 4264) nor cocaine (n = 3562). Conversely, significant increases in hospitalization [odds ratios (OR) = 1.023, 95% confidence interval (CI) = 1.004–1.041], ICU admission (OR = 1.080, 95% CI = 1.042–1.118) and in intubation (OR = 1.049, 95% CI = 1.001–1.099) were detected for lone heroin presentations (n = 1997). Sensitivity analysis (32 245 presentations, 14 EDs, 9 countries) confirmed the overall absence of changes in severity markers (except for death rate, which significantly decreased by quarter: OR = 0.968, 95% CI = 0.943–0.994). Additionally, it suggested an increased risk over time of intubation for cocaine (OR = 1.068, 95% CI = 1.009–1.130) and confirmed the increased risk of ICU admission for heroin (OR = 1.058, 95% CI = 1.013–1.105). Changes in severity over time did not differ according to sex in the main analysis of the whole cohort, while a significantly higher decrease in risk of death in men was found in the sensitivity analysis (OR = 0.894, 95% CI = 0.825–969 vs. OR = 0.949, 95% CI = 0.860–1.048; P interaction = 0.042). Conclusions: The severity of presentations to European EDs remained mainly unchanged during 2014–2019, but the risk of death may have decreased. Conversely, intubation in lone cocaine and ICU admission in lone heroin intoxications have increased. Although men and women exhibited a similar pattern over the period for the majority of comparisons, our data suggest that women exhibited a smaller decrease of the overall risk of death.